Genome-wide analyses of protein-DNA interactions - Farnham, Peggy (Henry Stewart Talks, 2007)
Identifying genomic targets of DNA-binding factors, Experimental methods, Chromatin immunoprecipitation (ChIP) assay, Probing microarrays, ChIP-on-chip assays for comprehensive analysis, Data interpretation and follow-up studies
Archived at 2015/07/13